Pengaruh Aktivitas Masyarakat Terhadap Kualitas Sungai Brantas - Novirina Hendrasarie; Risma Indah Salsabila (Prosiding ESEC, 2023)
The growth of population, agriculture and industries sector rapidly increaased in Branta river area causes an increase in use of river water so the risk of pollution increases. Some of parameter such as BOD, COD and TSS could be able to affect the water quality. With secondary data of BOD, COD and TSS from some of Brantas river’s checkpoint, Some points were obtained that exceeded the quality standard that is on first point located in Surabaya River with 320 mg/l of TSS, seond point located in Tengah River with 28,2 mg/l of COD, third point located in Porong River with 390 mg/l TSS and fourth point located in Brantas river with 15,6 mg/l of BOD. This is caused by the activities of the people around who pay little attention to the cleanliness of the river environment, such as throwing garbage on the banks of the river.